The Limits of Liberalism. Tradition, Individualism, and the crisis of freedom, Mark. T. Mitchell, University of Notre Dame Press, Indiana 2019, p. 328 — Review Article - Dzięcioł, Mateusz (Hybris, 2023)
In the reviewed book, Mark T. Mitchell presents a model for the critique of liberalism. The starting point for his argumentation is Michael Polanyi’s observation according to which the sources of political and spiritual crisis are the result of an incorrect conception of knowledge. This makes it impossible to formulate meaningful statements about categories, which we can identify as a Platonic Triad: truth, good, beauty. The book’s author also uses arguments from the field of religion. In the process of his argumentation, he claims that man needs God’s grace to overcome his imperfection, which is an inherent part of human nature. It is hard to question Mitchell’s book having value though it being erudite. Proposing to understand tradition in epistemic terms and making it a basis for the new social and political order are matters worth discussing in a broader fashion. However, certain methodological shortcomings of the book are apparent: an incomplete reconstruction of the positions being put forward, a lack of terminological distinctions that may cause semantic confusion, and the questionability of the assumptions being made. Therefore, Mitchell’s book should be viewed multidimensionally.